Penggunaan Kalimat Efektif dan Paragraf dalam Buku Teks Bahasa Indonesia di Sekolah Dasar 70 Libukang, Kecamatan Liliriaja Kabupaten Soppeng - Desy Ayu Andhira; Muhammad Dahlan (Dharma Acariya Nusantara: Jurnal Pendidikan, Bahasa dan Budaya, 2023)
This study aims to describe (1) effective sentences in Indonesian language textbooks in Elementary School 70 Libukang, Liliriaja District, Soppeng Regency and (2) the use of paragraphs in Indonesian language textbooks in Elementary School 70 Libukang, Liliriaja District, Soppeng Regency. This type of research is descriptive. The research data is the ineffectiveness of sentences and paragraph errors. Data were obtained from textbooks from class I to class VI. The data collection techniques for this research were documentation, literature study, and library research. The data analysis used in this study was descriptive qualitative analysis. The results of the study show (1) The use of effective sentences in Indonesian language textbooks at 70 Libukang Elementary School, Liliriaja District, Soppeng Regency is not in accordance with the rules and grammar of Standard Indonesian. This means that the sentences used are not effective in the preparation of the book. (2) The use of paragraphs in Indonesian language textbooks in Elementary School 70 Libukang, Liliriaja District, Soppeng Regency was found to be inconsistent with the requirements for paragraph preparation. The arrangement of paragraphs found was in the form of paragraphs that did not match the characteristics of completeness of paragraphs, disorganized sentences in paragraphs, incomplete sentences in paragraphs, and incoherence of paragraphs.